Otimização do processo de desidratação de folhas de cenoura (Daucus carota L.) visando a conservação de ácidos graxos ômega-3 - Almeida, Vanessa Vivian de (2007)
Most nutrients essential for human health come from vegetables. Vegetable parts that might be used, mainly due to their high nutritional value, are wasted for lack of knowledge of their use or of appropriate technologies for their industrialization. In this study, carrot leaf dehydration was optimized aiming at avoiding the degradation loss of alpha-linolenic acid (LNA, 18:3n-3). Carrot leaves were dried in vacuum and air-circulation oven. The optimization process was carried out in air-circulation oven with center-point full 22 factorial. It was investigated the influence of drying time and temperature on drying response (LNA concentration), which was estimated as the amount of LNA in mg/100 g of ground dehydrated carrot leaves by using the response surface methodology. The lipids, LNA and other fatty acids, were analyzed in a gas chromatographer coupled to a flame ionization detector with heneicosanoic acid methyl ester (21:0) as an internal standard. Carrot leaves dried in optimized conditions, 70 °C for 43 h, presented an average of 984.2 mg LNA per 100 g of dried matter. This value is higher than those estimated for carrot leaves dehydrated in other air-circulation oven drying conditions. The main fatty acids detect in ground dehydrated carrot leaves were: LNA, linoleic acid (LA, 18:2n-6), palmitic acid (16:0), and hexadecatrienoic acid (16:3n-3). The ratio between polyunsaturated fatty acids and saturated fatty acids (PUFA/SFA) was 3.19. The omega-6 sum and omega-3 sum ratio was 1:2.7. These results allow concluding that ground dried carrot leaves are a valuable source of essential fatty acids, especially of LNA as it is preserved when the leaves are dehydrated in optimized conditions. The addition of ground dehydrated leaves to soups, broths, and other dishes may raise their nutritional value and increase the availability of omega-3 in supplemented foods.